Frequency of Factors Responsible for Diabetic Retinopathy Among Patients of Type II Diabetes Mellitus - Nisar Ahmed Khan, Asma Shams, Narain Das, Riaz Ahmed Memon, Nadeem Memon, Abdul Haq Shaikh (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of factors responsible for diabetic retinopathy (DR) among patients with type II diabetes mellitus (DM). Materials and methods: This cross-sectional study was conducted at the department of Ophthalmology at Indus Medical College Tando Muhammad Khan from January 2021 to June 2021. Patients having type II diabetes mellitus, aged > 40 years, presenting with diabetic retinopathy of either gender were included. After dilating the eye with a 1% tropicamide eye drop, skilled and experienced ophthalmologists diagnosed diabetic retinopathy by using the 90 diopter Volk lens and a slit lamp biomicroscope. A 5 mL blood sample was obtained and sent to the diagnostic laboratory to assess the random blood sugar (RBS) and HBA1c. All the data was collected by using the study proforma and SPSS version 26 was used for the data analysis. Results: A total of 66 patients with diabetic retinopathy were evacuated regarding risk factors. Most of the patients (68.2%) were old. Males were in the majority 75.8%, and females were 24.2%. Out of all, 56.1% patients were poor socioeconomically, while 65.2% were smokers. Half of the patients had microalbuminuria and 68.2% of the cases had HBA1c > 7, while 22.7% of the cases were hypertensive. Most of the cases (66.7%) had a duration of diabetes of more than 10 years. Conclusion: We concluded in this study that age greater than 60 years, low socioeconomic status, smoking, diabetes duration greater than 10 years, HBA1c greater than 7, and microalbuminuria were found to be significant prognostic factors for diabetic retinopathy. As per several study limitations, further large-scale case control studies on particular risk factors are recommended.